Предмет:
МатематикаАвтор:
анонимОпределим, каким одночленом надо заменить звездочку, чтобы выполнялось равенство:
1) * x 3b^(4) = 12b^(6);
4 * 3 * b^(4) = 12 * b^(6);
2) -5a^(5)b^(2) x * = -20a^(6)b^(8);
-5 * a^(5) * b^(2) * 4 * a * b^6 = -20 * a^(6) * b^(8);
3) -7a^(3)b^(9) x * = 4,2a^(5)b^(12);
-7 * a^(3) * b^(9) * (-0.6) * a^2 * b^3 = 4,2 * a^(5) * b^(12);
4) 23a^(12)b^(16) x * = -23a^(29)b^(17);
23 * a^(12) * b^(16) * (-1) * a^17 * b = -23 * a^(29) * b^(17).
Автор:
rolandowyattДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть